TRANSFORMASI DIGITAL ERA INDUSTRI 4.0 REVOLUSI ‎LAYANAN YANG MENGUBAH LANSKAP PERBANKAN SYARIAH ‎DI INDONESIA - Bagas Dwi Arifin; Muhammad Iqbal Fasa‎ (Cipta Kind Publisher, 2024)
This study examines the digital transformation in the context of Islamic banking services revolution in Indonesia. Employing a qualitative research method based on a literature review, this research analyzes the implementation of digital technologies, their impact on Islamic banking performance, and the factors influencing the success of digital transformation. The findings reveal that digital transformation has introduced various service innovations such as mobile banking, internet banking, and digital payment systems, enhancing operational efficiency and accessibility of Islamic banking services. However, the transformation faces challenges including limited human resources, cybersecurity, regulations, and financial literacy among the public. Key success factors include technological innovation, effective risk management, collaboration with fintech, development of digital infrastructure, enhancement of human resource competencies, and appropriate regulatory support. This study provides valuable insights for developing digital transformation strategies in Islamic banking that align with Shariah principles and the demands of the digital era. Keywords: Digital transformation, Islamic banking, Industry 4.0, Fintech, Digital technology